KUALITAS PELAYANAN DINAS KEPENDUDUKAN DAN CATATAN SIPIL DALAM PEMBUATAN DOKUMEN KEPENDUDUKAN: Suatu Penelitian Tentang Pelayanan Dinas Kependudukan Dan Catatan Sipil Dalam Pembuatan Dokumen Kependudukan di Kota Bogor Tahun 2022 - egy widyatmoko; Harianto; Retno iswati (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
The focus of this research is the quality services of Population and Civil Registry regarding the preparation of residence documents in Bogor City. The purpose of this research is to measure the Quality of the Service at the Population and Civil Registry in Bogor City on 2022. The theory used in this study is the Five Dimensional SERVQUAL theory according to Zeithaml, Parasuraman, and Berry in Ratminto and Winarsih which adjusted the standard operating procedures for services and policies written by the Bogor City Population and Civil Registry Service. The method used is descriptive quantitative. The population of this research is the people who make population and civil registration documents at Disdukcapil Bogor City with a sample size of 100 people. Data collection was carried out by distributing questionnaires, observation and documentation. The sampling technique uses accidental sampling. The suggestion for this research is that the Bogor City Disdukcapil is expected to be able to improve the quality of its services to the community as service users, especially in terms of speed and accuracy, the Bogor City Disdukcapil needs to provide good physical appearance and provide more adequate supporting facilities, the Bogor City Disdukcapil is expected to increase its socialization regarding the application "Si Kancil Berlari" so that people can find out and use the application so that it can facilitate and assist the community in making population documents and civil registration